Increased susceptibility of RAG-2 SCID mice to dissemination of endodontic infections. - Teles, R (1997)
Specific immunity has been implicated in the pathogenesis of periapical lesions, although the extent to which these mechanisms are actually involved in either protection or destruction of the pulp-periapex complex is yet to be established. To investigate this question we compared periapical-lesion pathogenesis in RAG-2 severe combined immunodeficient (SCID) mice with immunocompetent control mice following surgical pulp exposure. In order to equalize the bacterial challenge, an infection protocol using Prevotella intermedia, Fusobacterium nucleatum, Peptostreptococcus micros, and Streptococcus intermedius was devised. The results demonstrated that after infection, the proportion of the root canal flora represented by the four pathogens was almost identical in both groups (39.9 and 42.2% for RAG-2 and immunocompetent control mice, respectively). The effects of abrogation of T- and B-cell mechanisms on periapical pathogenesis were then assessed. Approximately one-third of the RAG-2 mice developed endodontic abscesses, while no immunocompetent controls had abscesses, results which indicated regional dissemination of the infection. A similar incidence of abscesses was found in two additional experiments. Abscessed RAG-2 teeth had significantly larger periapical lesions than did nonabscessed RAG-2 teeth (P < or = 0.05) and exposed immunocompetent controls (P < or = 0.01), whereas nonabscessed RAG-2 teeth were not significantly different from those of exposed immunocompetent controls in periapical-lesion size. We conclude that B- and T-cell-mediated immunity protects the host from the dissemination of endodontic infections and that RAG-2 mice are more susceptible to infection-induced pulp-periapex destruction.